Dinâmica de comunidades de formigas forrageadoras epigéicas em fragmentos de mata seca do cerrado - (:unkn) unknown (Universidade Estadual de Goiás, 2018)
One of the main consequences of anthropogenic disturbances is the fragmentation of natural environments. Much of the natural vegetation of the Brazilian Cerrado is in the form of small fragments, highly disturbed, isolated and little studied. Mainly due to large-scale agriculture with soybean and corn crops, the Cerrado areas of the southeastern region of Goiás fall into this scenario. Due to their peculiarities, the ants have been used as bioindicators of environmental quality, mainly in degraded areas. The objective of this work was to characterize the structure of the epigeic foraging ant communities in distinct fragments of Dry Forest and their respective environmental matrices (agricultural areas: during the harvest, onset, and off-season) in the southeastern region of Goiás. The method of capture of the formicides was that of traps with baits. The faunal indexes of the ants communities captured in the fragments and their respective matrices were correlated in three distinct moments: Dry Forest fragments surrounded by agricultural crops during the harvest (soybean), little crop (corn) and off-season. We investigated 10 MS fragments, with areas varying from 4.22 to 44.4 ha. Throughout the study, 60 ant morphospecies were collected, distributed in 7 subfamilies and 21 genera. The subfamily with the highest number of species was Myrmicinae (24), followed by Formicinae (19), Ponerinae (6), Ectatomminae (4), Dolichoderinae (4), Pseudomyrmecinae (2) and Heteroponerinae (1). The most frequently captured genera were: Camponotus and Pheidole, with 15 and 9 morphospecies, respectively. It was observed a significant difference in the richness of epigeic ants in Dry Forest environments and in the environment matrix with soy, maize and off-season. Dry Forest presented a mean of 21.1 morphospecies and environment matrix, 10.8 morphospecies. The size of the Dry Forest fragment did not significantly influence the richness of ants. However, the similarity of the ants communities, as measured by the Jaccard Index, showed two distinct groups in DF and matrices of environments and also in the set of ants captured in DF and matrices of environment, in crop, little crop and off-season. Our results suggest that the richness and composition of ant communities can be used as a monitoring tool for anthropogenic habitat alterations.
Keywords: Formicidae; Fragmentação; Riqueza; Similaridade; Formicidae; Fragmentation; Richness; Similarity; CIENCIAS AGRARIAS